Antibacterial potential of Biduri leaf extract (Calotropis gigantea) against the growth of Streptococcus mutans ATCC 35668 colonies: an experimental laboratory - Kholidiya, Wulan Ratna Nur; Meilawaty, Zahara; Astuti, Pudji (Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Caries is an oral cavity infection that attacks the hard tissue of the teeth. Caries are caused by cariogenic bacteria such as Streptococcus mutans (S.mutans). S.mutans plays a role in the process of biofilm and plaque build up. One alternative ingredient that has antibacterial properties is Biduri leaves (Calotropis gigantea). The research aimed to analyze the antibacterial potential of Biduri leaf extract on the growth of S.mutans colonies. Methods: This type of research is a laboratory experimental research in vitro using the post-test-only control group design method. The antibacterial test used the colony counting method. The extraction process used the maceration method for 1 day with a shaker. The concentrations used were concentrations of 20, 40, and 60%. Control (+) used 0.2% chlorhexidine and control (-) used distilled water. Incubation process was for 24 hours. Counting the growth of S.mutans colonies using a colony counter was carried out by three observers. Data analysis used the Kruskal-Wallis test followed by the Mann-Whitney test. Results: The results showed that there was a significant difference in the growth of S.mutans (p<0.05) after being exposed to Biduri leaf extract at a concentration of 20, 40, and 60%. Conclusion: The Biduri leaf extract has antibacterial potential against S.mutans at concentrations of 20, 40, and 60%, and the best concentration in reducing the growth of S.mutans colonies is the concentration of 60%.KeywordsAntibacterial, Calotropis gigantea, 0.2% chlorhexidine, colony counting, Streptococcus mutans